The Relationship between Transformational Leadership and Learning Organization on Professional Commitment - Wilian, Dwi; Hidayat, Rais; Karmila, Nita (Universitas Pakuan, 2023)
The objective is to determine the relationship between transformational leadership and learning organization toward teachers' professional commitment and implemented recommendations for related parties. The population in this study was 141 private high school teachers in the Cibinong District using the Slovin formula. Data collection for each variable was studied using a questionnaire with a Likert scale. Data analysis used the Statistical Program for Social Science SPSS 26. The results showed: (a) There is a positive and significant relationship between transformational leadership and professional commitment. The correlation coefficient value is ry1 = 0.735, (b) There is a positive and meaningful relationship between learning organization and professional responsibility. The correlation coefficient value is ry2 = 0.739, (c). There is a positive and significant relationship between transformational leadership and learning organization in conjunction with professional commitment. The general form of multiple regression used a value of ry12 = 0.784 was obtained. Principal support and convenience in the digitalization era make it possible for teachers to share information. The use of technology by teachers to share teaching methods or techniques with fellow teachers from different organizations is possible without space and time limitations. Self-development achieved by teachers shows professional commitment and will increase competence as professional educators.